Improving The Subjective Well-Being Of Kindergarten Teachers: A Strategic Step Towards Achieving The SDGs On Education And Welfare - Sagita, Dony Darma; Simarmata, Sari Wardani; Saputri, Novi Eka; Fathurrachman, Saddam; Kasmiarno, Kurnia Sari (Educational Guidance and Counseling Development Journal, 2024)
This study aims to analyze the Subjective Well-Being (SWB) of kindergarten teachers in DKI Jakarta and its implications for the quality of early childhood education in achieving the Sustainable Development Goals (SDGs). We employed a quantitative descriptive approach, surveying a sample of 380 kindergarten teachers in DKI Jakarta. To measure aspects of self-satisfaction, positive affection, and negative affection, we utilized the Teacher Subjective Wellbeing Questionnaire (TSWQ). The results indicated that 68.6% of teachers reported a moderate level of SWB, while 16.2% fell into the low category and 15.2% exhibited a high level of SWB. These findings underscore the importance of subjective well-being for teachers, as it not only impacts their performance but also serves as a reference for fulfilling the SDGs in education. Teachers with a high SWB are likely to foster a more positive and high-quality learning environment, whereas those with low well-being may struggle in this regard. This study recommends enhancing social support, providing ongoing professional training, implementing performance awards, and promoting work-life balance as strategies to improve teacher SWB and support sustainable development in education